(untitled) (Perner’s Contacts, 2009)
The paper deals with problem of determination of coefficients of road vehicles on the basis of measuring of entry times. This paper is based on results of activities in Laboratory of Road Transport (Institute of Transport, VSB-TU Ostrava).